The Use of Prophylaxic Antibiotics in Patients with Caesarean Section in the Inpatient Installation of Cibinong Regional General Hospital in the Period of January - December 2023 - Saifana, Qanita; Lilian Batubara; Dharma Permana (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Postoperative infections after cesarean section (CS) remain a major concern, increasing morbidity, hospitalization duration, and healthcare costs. Prophylactic antibiotics are an important preventive measure, but their effectiveness depends on appropriate type, dose, timing, and adherence to guidelines. This study evaluated prophylactic antibiotic use in CS patients at Cibinong Regional General Hospital (RSUD). Methods: A descriptive cross-sectional study analyzed medical records of 81 CS patients from January to December 2023. Data on antibiotic type, dose, timing, and clinical outcomes were assessed against hospital, POGI, and ASHP guidelines. Results: All patients received prophylactic antibiotics. Cefazolin was most commonly used (61.7%) and showed the highest effectiveness, with no infections among 50 patients. In contrast, ampicillin, gentamicin, and metronidazole were less effective, with infection rates of 26.7%, 100%, and 100%, respectively. Overall, 24.7% of patients developed postoperative infections. Discussion: Findings highlight cefazolin’s superiority, consistent with international guidelines recommending it as first-line prophylaxis for CS. Variations in antibiotic selection, dosing, and timing were linked to higher infection rates, emphasizing that protocol inconsistencies reduce effectiveness. Risk factors such as maternal age, obstetric history, and indication for CS may also influence outcomes. Conclusion: Prophylactic antibiotic use at Cibinong RSUD generally followed guidelines, with cefazolin proving most effective. However, inconsistent practices in dosage and timing contributed to a notable infection rate, underscoring the need for stricter adherence to standards.